Mapping the global research output on Ebola vaccine from research indexed in web of science and scopus: a comprehensive bibliometric analysis - Tosin Yinka Akintunde; Taha Hussein Musa; Hassan Hussein Musa; Shaojun Chen; Elhakim Ibrahim; Sayibu Muhideen; Joseph Kawuki (Taylor & Francis Group, 2021)
Introduction: The Ebola Virus outbreak in Africa is believed to be one of the deadliest viral infections that causes severe hemorrhagic fever in human and nonhuman primates, which has resulted in increased mortality rates in the affected African countries. Thus, the current study mapped and quantified global research output and trends in the EBOV vaccine publications via a bibliometric analysis. Methods: Publications about the Ebola virus vaccine were extracted from the Web of Science and Scopus databases. HistCite, Bibliometrix, an R package, and VOSviewer.Var1.6.6 were used for data mapping and analysis. Results: A total of 541 (WoS) and 511 (Scopus) documents were included, with a cumulation of 24,611 citations in both databases. These documents were published in 141 journals in the Wos and 185 in Scopus. The USA was the most productive country with 206 (38.08%) publications in the Wos. Although the top-cited authors are from the USA, the United Kingdom, and Canada, only one author from Africa "Samai M" from the University of Sierra Leone contributed 13 publications. Meanwhile, the Journal of Infectious Diseases was the most productive (45, 8.32%) in this field. Conclusion: The study provides insight for researchers and health policy on the trends and progress of the EBOV vaccine research and development, focusing on the hot topics, research collaboration, and research dearth that requires urgent redress to fast-track an all-inclusive EBOV vaccine development.